Potensi dan Strategi Pengembangan Objek Wisata Tahura Lapak Jaru Kuala Kurun Kabupaten Gunung Mas Provinsi Kalimantan Tengah - Herianto; Abdul Mukti; Renhart Jemi (Journal of Environment and Management, 2020)
Conservation areas are known for their significant functions to protect the plant and animal biodiversity, as well as their ecosystems. Lapak Jaru Tahura, which is located in Gunung Mas Regency, Central Kalimantan, is one of the conservation areas with potential ecotourism attraction. The strategy for developing tourist objects and natural attractions in Tahura Lapak Jaru needs to be formulated to gain positive impact and to reach its sustainability. The purpose of this study was to dig ecotourism potential in Tahura Jaru Kuala Kurun and to formulate tourism development strategies in the Tahura Lapak Jaru in Kuala Kurun tourist area. This research was conducted through 2 (two) stages of analysis. First, identifying the tourism potential in the Tahura Jaru Kuala Kurun area with descriptive analysis. Second, formulating a tourism development strategy in the Tourism Area of the Lapak Jaru Kuala Kurun tourism area with a SWOT analysis. The results showed that the Lapak Jaru Tahura is a very potential site for further development to become a tourist attraction. The strategy of Tahura Lapak Jaru development is aggressive, namely, to use the strength they have to take advantage of current opportunities. These strategies, among others, are, first, to maintain its position as a tourism destination which fully supported by local government and the ease of gaining potential investor. Second, regional development planning needs to include the participation of local communities so that target consumers who tend to like nature tourism can be achieved.